In vitro test of antibacterial activity causing inhibition of wound healing from ethanol extract of nangka (Artocarpus heterophyllus, Lam.) leaf - Esther Siringo-ringo; Indah Yani Tambunan; Mastiur Julianti Butar-butar; Kasta Gurning; Iksen Iksen (Pascasarjana Universitas Negeri Medan, 2023)
Nangka (Artocarpus heterophyllus, Lam.) is a plant that is rich in nutrients and contains phytochemicals that can be used in various fields, especially in the health sector. Traditionally, every part of this plant has been widely used for its anticarcinogenic, antimicrobial, antifungal, anti-inflammatory, wound healing, and hypoglycemic effects. Antibacterials are an important part of drug preparations to accelerate wound healing. Antibiotics inhibit the occurrence of infection and stimulate the process of forming fibroblast cells for wound closure. Bacteria that are often found in wounds and inhibit the acceleration of wound healing are Staphylococcus aureus and Escherichia coli. The purpose of this study was to test the activity of the ethanol extract of nangka leaf (Artocarpus heterophyllus, Lam.) in vitro on E. coli and S. aureus bacteria. The extraction method used was maceration with ethanol solvent and in vitro antibacterial activity testing using the paper disc method, as well as variations in extract concentrations, namely 12.5%, 25%, 50%, 75%, chloramphenicol as a positive control, and 5% DMSO as a negative control. The results showed that the ethanol extract contained various secondary metabolites, namely alkaloids, tannins, saponins, steroids/triterpenoids, and flavonoids. The ethanol extract of nangka leaf (Artocarpus heterophyllus, Lam.) has strong category potential as an antibacterial against E. coli and S. aureus.Keywords: Antibacterials; Escherichia coli; Nangka leaf; Staphylococcus aureus; Wound healing